PENGEMBANGAN BAHAN AJAR DENGAN KONTEKS ALAT BERBURU TRADISIONAL DAYAK TABUN DALAM MATERI BANGUN RUANG - Hedrian Pilimon; Muhamad Firdaus; Hartono Hartono (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2021)
This study aims to determine "How is the development of teaching materials with the context of traditional Dayak tabun hunting tools in the flat-sided building material for class VIII students of SMP Negeri 01 Ketungau Tengah". With sub-problems or problems, especially in this study, how is the level of validity, practicality, and effectiveness of teaching materials in the context of traditional Dayak tabun hunting tools in the material for building flat-sided spaces in class? VIII students of SMP Negeri 01 Ketungau Tengah. The method used in this study is the Research & Development (R&D) research method concerning the 4-D model, namely Define, Design, Development, and Disseminate. The test subjects in this study were class VIII students of SMP Negeri 01 Ketungau Tengah, with 29 students. Based on the results of the limited trials conducted, it was found that 1) the results of the validation of teaching materials were 80.79% in the excellent category, 2) the results of practicality based on observations of the implementation of the teaching materials developed were 84.37% in the practical category, 3) the results of the effectiveness of the materials. Teaching is 68.96 % with effective category. So, it can be concluded that in the limited trial stage, mathematics teaching materials in the context of traditional Dayak tabun hunting tools have met the criteria of validity, practicality, and effectiveness